Tracing HRD’s Rational Masculine Roots: Feminist Alternatives for a More Mindful HRD - Laura L. Bierema; Julia Storberg-Walker (Adult Education Research Conference, 2007)
A classic management text was deconstructed using postmodern methods to illuminate the connections between knowledge and gender. A similar analysis was performed on a selected contemporary HRD course text in order to examine how issues related to performance and gender were being addressed.